Kinetics of carbon dioxide absorption into aqueous MDEA+bmimBF 4 solutions from 303 to 333K - Ahmady, A.; Hashim, M.A.; Aroua, M.K. (Elsevier, 2012)
The kinetics of CO 2 absorption in aqueous solutions of MDEA+bmimBF 4 were investigated using a stirred cell reactor where the relevant parameters were evaluated. The rate equation of the absorption reaction was found to be close to first order with respect to CO 2 at temperatures ranging from 303 to 333K and bmimBF 4 concentration from 0 to 2.0molL -1. The activation energy decreased from 43.32kJmol -1 to 8.65kJmol -1 with increasing bmimBF 4 concentration from 0 to 2.0molL -1 in aqueous 4molL -1 MDEA solution. Calculated results of the enhancement factor and Hatta number showed that the performance of CO 2 absorption in the aqueous 4molL -1 MDEA+bmimBF 4 solution almost obeyed the pseudo first order regime.